PEMANFAATAN POHON LOBA (Symplocos fasciculata Zoll.) SEBAGAI PEMBANGKIT WARNA ALAM PADA KERAJINAN TENUN DI DESA PEJENG, TAMPAK SIRING, GIANYAR, BALI - SF Hanum; IDP Darma; IMd Sumerta (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Indonesia's plant diversity potentially as natural dyes. A general process in dyeing with natural dyes needed mordanting workmanship on the material to be dyed/stamped. The process of mordanting is done by immersing the material into the metal salts, such as aluminum, iron,tin or chrome. Amid fears of negative impacts caused by dyes and synthetic mordant to health and the environment, people begin to look back the use of natural dyes. So far, the material used for mordanting is alum; though Loba tree (Symplocos fasciculata Zoll.) is one type of plant that can be useful as mordant but today not many people knows the role of this plant. This paper aims to determine the S. fasciculata role and its use as mordant for natural dye textiles. The method used was interviews with parties concerned. The results of this research is aknowledge on S. fasciculata role as a mordant as local wisdom in traditional Balinese weaving. Plant parts that may be used are leaves and inner bark. Conservation efforts is eagerly continued by Eka Karya Bali Botanic Gardens-The Indonesian Institute of Science (LIPI). Currently two species (among 250 naturally grow) of Symplocos conserved at Eka Karya Bali Botanic Garden-LIPI.